2007
DOI: 10.1103/physreva.75.011802
|View full text |Cite
|
Sign up to set email alerts
|

Universal output directionality of single modes in a deformed microcavity

Abstract: Experimental investigation of the characteristics of quasi-bound states of a quadrupole deformed microcavity has revealed five distinct mode groups in cavity emission spectra with cavity quality factors different by orders of magnitude and consistently with much different intracavity mode distributions but with almost universal far-field emission patterns. These universal directionality of high Q modes are explained by a subtle manifestation of unstable manifolds of classical chaos in the formation of quasi-bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 27 publications
(28 reference statements)
2
30
0
Order By: Relevance
“…In fact, the same -X dependence was observed for the other P modes and even at off resonance as well, which is consistent with the mode-independent farfield patterns shown in Ref. [26]. A maximum pumping efficiency occurs at ð; XÞ ¼ ð55…”
Section: H Y S I C a L R E V I E W L E T T E R Ssupporting
confidence: 89%
See 2 more Smart Citations
“…In fact, the same -X dependence was observed for the other P modes and even at off resonance as well, which is consistent with the mode-independent farfield patterns shown in Ref. [26]. A maximum pumping efficiency occurs at ð; XÞ ¼ ð55…”
Section: H Y S I C a L R E V I E W L E T T E R Ssupporting
confidence: 89%
“…We can identify five distinct mode groups with mode orders l ¼ 1, 2, 3, 4, 5 as shown in Fig. 1(b), a magnified view of the spectrum in the region of 600 nm [26]. Each of the mode groups has a regular mode spacing, supporting that the observed modes are localized on periodic orbits.…”
Section: H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 54%
See 1 more Smart Citation
“…In another way, the rays motion near the critical line have all been domain by the unstable manifold near it, and a direct result is that high Q modes will all have the similar directionality because they obey the same motion when they leak out, leading to the so-called university directionality emission. This has been proven in varied cavity shape in both experiment and numerical simulation [40,41].…”
Section: Mechanism Of Directional Emissionmentioning
confidence: 76%
“…This result is important because this mechanism can be applied to other high-Q modes in chaotic microcavity. The importance of unstable-manifold structure near the critical line has been stressed by many authors (Schwefel et al, 2004;Altmann, 2009) and experimentally confirmed in liquid-jet microcavity (Lee, S.-B. et al, 2007).…”
Section: Scarred Modesmentioning
confidence: 99%